SATISFACTION OF PATIENTS ATTENDING TO THE DENTAL CLINIC OF THE SAN MARTIN DE PORRES UNIVERSITY. CHICLAYO, 2015 - Córdova -Sotomayor, Daniel (2016)
Objectives. To determine the level of satisfaction of patients attending the Dental Clinic of the San Martin de Porres University;Chiclayo - 2015. Materials and methods: The present study was non-experimental, descriptive, and prospective and cross-sectionalperformed during October 2015 in a population of 60 patients attending to the Dental Clinic of the San Martin de Porres University –North Subsidiary; the data to determine the level of satisfaction was obtained by applying a previously validated questionnaire. For dataanalysis, descriptive statistics were used. Results: Regarding the level of satisfaction of patients attending to the Dental Clinic of theSan Martin de Porres University, 76.7% qualified it as good and 23.3% as regular. Conclusions: The results obtained in this studyshowed that the services provided by the Dental Clinic of the San Martin de Porres University were rated by patients as good bothwarmth and quality of care. Gene